(untitled) (Nóema, 2017)
This article intends to briefly analyze the characteristics that the form of the essay assumes in György Lukács, Walter Benjamin and Theodor W. Adorno’s thought. I focused on one single point: the central function that the essay acquires within the relations between particulars and system. The results are particularly interesting since, in the face of a substantial agreement on initial diagnosis, the three autors propose very different solutions: Lukács intends the form of the essay as the only possible way to overcome the fracture between world and totality; on the contrary, Adorno intends that same form as the only form adequate to express the insurmountability of the fracture; finally, Benjamin tries to keep both sides togheter: the autonomy of the trascendent and the salvation of the immanent.